Endoscopic and clinicopathological characteristics of colorectal T/NK cell lymphoma - Hideki Ishibashi; Satoshi Nimura; Fumihito Hirai; Naohiko Harada; Hiromi Iwasaki; Sigeto Kawauchi; Yumi Oshiro; Atsuji Matsuyama; Shotaro Nakamura; Yasushi Takamatsu; Hirotoshi Yonemasu; Taturo Shimokama; et al. (BMC, 2020)
Abstract Background Colorectal T/natural killer (NK)-cell lymphomas (TNKCL) are very rare. Endoscopic and clinicopathological characteristics of colorectal TNKCL have not been clearly demonstrated. In this study, we demonstrated the clinical characteristics of colorectal TNKCL. Methods Endoscopic and clinicopathological characteristics were investigated in 27 patients with colorectal monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL), adult T-cell leukemia/lymphoma (ATLL), and other types of TNKCL. Results Nine TNKCL patients (33%) were classified as MEITL, 11 (41%) as ATLL, and seven (26%) as other. Four patients with Epstein-Barr Virus-positive (EBV+) TNKCL, two indolent T-cell lymphoproliferative disorder and one anaplastic large cell lymphoma were included in the other group. Endoscopically, six MEITL (67%) and five ATLL (46%) showed diffuse-infiltrating type, in which the main endoscopic lesion was edematous mucosa in MEITL, while aphthoid erosion and edematous mucosa were typical in ATLL. Ulcerative type was identified in four other group patients (57%), including two EBV+ TNKCL. An increase in atypical T-intraepithelial lymphocytes (T-IELs) was noted in seven MEITL (88%) and six ATLL (60%) patients, but not in the other group (0%) patients. Five MEITL patients (56%) showed features of lymphocytic proctocolitis with increased CD8+ T-IELs. Conclusions MEITL and ATLL occasionally invaded the colorectum, and primary involving MEITL was observed. Diffuse infiltrating type was the characteristic endoscopic finding in colorectal MEITL and ATLL, while ulcerative type was observed in the other group. Features of lymphocytic proctocolitis may be prodromal findings of MEITL.